Hysteresis as a probe of turbulent bifurcation in intrinsic rotation reversals on Alcator C-Mod. (29th August 2019) - Cao, N.M.; Rice, J.E.; Diamond, P.H.; White, A.E.; Baek, S.G.; Chilenski, M.A.; Hughes, J.W.; Irby, J.; Reinke, M.L.; Rodriguez-Fernandez, P.
Abstract: Analysis and modeling of a new set of rotation reversal hysteresis experiments unambiguously show that changes in turbulence are responsible for the intrinsic rotation reversal and the linear to saturated ohmic confinement (LOC/SOC) transition on Alcator C-Mod. Plasmas on either side of the reversal exhibit different toroidal rotation profiles and therefore different turbulence characteristics despite profiles of density and temperature that are indistinguishable within measurement uncertainty. The deactivation of subdominant (in linear growth rate and heat transport) ion-temperature gradient and trapped electron mode-like instabilities in a mixed-mode state is identified as the only possible change in turbulence within a quasilinear transport approximation across the reversal which is consistent with the measured profiles and the inferred heat and particle fluxes. This indicates an explanation for the LOC/SOC transition that provides a mechanism for hysteresis through the dynamics of subdominant modes and changes in their relative populations, and does not involve a change in most (linearly) unstable ion-scale drift-wave instability.